2013
DOI: 10.1007/s11104-013-1627-y
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical cycling of soil phosphorus during natural revegetation of Pinus sylvestris on disused sand quarries in Northwestern Russia

Abstract: Background and aims Quarrying causes severe degradation of soils and forest cover that can be recovered partially when the quarries are abandoned and re-colonised by plants. To understand the recovery of soil functionality and nutrient cycling, we studied the development of soil phosphorus pools during Scots pine (Pinus sylvestris) revegetation in a disused sand quarry in Northwestern Russia. Methods Sites that had been developing for different times since abandonment were compared to the parent sand and an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 64 publications
2
30
0
Order By: Relevance
“…The pace of P transformations at Haast is driven by the warm, wet climate, the relatively low initial total P pool, and the coarsetextured soil. Similar rapid depletion of apatite has been reported for a number of other chronosequences on sandy soils (Syers and Walker 1969;Singleton and Lavkulich 1987;Celi et al 2013). At the nearby Franz Josef chronosequence, where soils are developed on post glacial deposits and develop into finetextured soils, the rate of decline in total P is similar to Haast, but total P concentrations remain high for a much longer period of time due to the greater initial P concentration in the schist/greywacke parent material (Walker and Syers 1976;Turner et al 2012b).…”
Section: Patterns Of Phosphorus Forms and Concentrations Along The Chsupporting
confidence: 71%
“…The pace of P transformations at Haast is driven by the warm, wet climate, the relatively low initial total P pool, and the coarsetextured soil. Similar rapid depletion of apatite has been reported for a number of other chronosequences on sandy soils (Syers and Walker 1969;Singleton and Lavkulich 1987;Celi et al 2013). At the nearby Franz Josef chronosequence, where soils are developed on post glacial deposits and develop into finetextured soils, the rate of decline in total P is similar to Haast, but total P concentrations remain high for a much longer period of time due to the greater initial P concentration in the schist/greywacke parent material (Walker and Syers 1976;Turner et al 2012b).…”
Section: Patterns Of Phosphorus Forms and Concentrations Along The Chsupporting
confidence: 71%
“…Despite the less important roles of climate and P inputs, we found that the amount of variance of the PAC explained by the interactive terms of these three factors was largest (Fig 2), suggesting that climate and P inputs alter the soil factors [46] and subsequently affect the PAC.…”
Section: Discussionmentioning
confidence: 97%
“…In consequence, the degree of P saturation of the soil sorbents decreased with increasing soil depth (S6). In contrast, several studies showed translocation of P by podsolization (Turner et al 2012;Wu et al 2014;Celi et al 2013;Wood et al 1984), especially in cold temperate climate (Väänänen et al 2008). Also Backnäs et al (2012) observed P translocation from topsoil to subsoil horizons during podsolization.…”
Section: Phosphorus Associated To Al and Fe Oxy(hydr)oxidesmentioning
confidence: 96%